Controlled Synthesis of CuInS2/ZnS Nanocubes and Their Sensitive Photoluminescence Response toward Hydrogen Peroxide - Kim, Youngsun; Jang, Ho Seong; Kim, Hyunki; Kim, Sehoon; Jeon, Duk Young (American Chemical Society, 2017)
We synthesized uniform CuInS2/ZnS nanocubes by adjusting reaction parameters at the ZnS growth stage. Higher temperature and zinc concentration were shown to drive resultant crystals to have cubic morphology, which could be ascribed to the facet-dependent ligand dynamics on the crystal surface and concomitantly preferred directions of crystal growth. It was found that these nanocubes exhibit sensitive responses, as of photoluminescence quenching, toward hydrogen peroxide, compared to pyramid-shaped nanocrystals. The origin of quenching was further analyzed to be the oxidation of thiolate ligands that leaves the quenching center on the surface. It was noted that the quenched photoluminescence could be fully recovered by introducing additional ligand molecules into the system. Being adopted in the shape-controlled crystal growth, the ligand-to-crystal interaction was shown to still govern the interfacial reaction, the oxidation by hydrogen peroxide, of faceted crystals in our system. It turns out that the reactivity at the crystal surface depends on the exposed facets, especially induced by shape control, and the weak ligand-binding nature of the nanocube renders it vulnerable to the surface reaction.
Keywords: ONE-POT SYNTHESIS; COLLOIDAL SEMICONDUCTOR NANOCRYSTALS; QUANTUM DOTS; SHAPE CONTROL; CDSE NANOCRYSTALS; IN-VIVO; PRECURSOR INJECTION; GROWTH; ELECTROOXIDATION; NONINJECTION